Fluorinated porous silicon as sensor material for environmentally toxic gases: a first-principles study. Issue 3 (22nd January 2021) - Santana, José Eduardo; de Santiago, Francisco; Miranda, Álvaro; Pérez, Luis Antonio; Salazar, Fernando; Trejo, Alejandro; Cruz-Irisson, Miguel
Abstract : Theoretical study of the adsorption of environmentally harmful molecules on fluorinated porous silicon. Abstract : By using Density Functional Theory, the effect of adsorbed gas molecules on the electronic properties of fluorine passivated porous silicon (pSi) is investigated. A silicon nanopore is created by removing columns of atoms along the [001] crystallographic axis from a supercell of the bulk Si crystal. The Si dangling bonds of the generated pore are saturated with fluorine atoms except for the sites where gas molecules of NO, NO2 and SO2 are adsorbed. The adsorption energies, electronic densities of states and band structures of the different complexes formed by the nanopore and the adsorbed molecules are calculated and compared with previously reported results obtained for hydrogen-passivated pSi. The energy band gaps of the pSi-molecule complexes depend on the adsorbed species, opening the possibility of gas molecule recognition. The molecule adsorption energy is stronger for NO2 . The understanding of molecule adsorption on silicon nanopores could lead to the development of novel sensing devices of environmentally hazardous gases.